1992
DOI: 10.1001/archsurg.1992.01420090060009
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Patient With a Knee Dislocation

Abstract: One hundred fifteen patients with a unilateral knee dislocation underwent arteriography to examine the popliteal artery. The incidence of popliteal artery injury was 23% (27 patients). Clinically, 29 (25%) of the 115 patients had an abnormal ipsilateral pedal pulse and 23 (79%) of these 29 patients had an arteriographically identified popliteal artery injury. Twenty-two arteries were surgically repaired and one was treated without surgery. Eight-six patients had normal pulses; the arteriogram showed no abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
97
0
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(101 citation statements)
references
References 28 publications
0
97
0
4
Order By: Relevance
“…In previous studies, the percentage of vascular injuries diagnosed requiring surgical treatment ranged from 64% to 100% [1,5,10,14,[16][17][18]20]. The lower proportion of vascular injury undergoing surgery from our data is interesting since vascular injury secondary to knee dislocation may be severe with a high potential for limb loss [2,7,9,13,15].…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…In previous studies, the percentage of vascular injuries diagnosed requiring surgical treatment ranged from 64% to 100% [1,5,10,14,[16][17][18]20]. The lower proportion of vascular injury undergoing surgery from our data is interesting since vascular injury secondary to knee dislocation may be severe with a high potential for limb loss [2,7,9,13,15].…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, it is important to understand the epidemiology of these events. Previous studies vary widely on the reported frequency of vascular injuries in patients with knee dislocations, ranging from 5% to 64% [5,11,[13][14][15][16][17][18][19]. This can most likely be attributed to the small sample sizes used in the majority of these studies, as knee dislocations are relatively rare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knee dislocation is often associated with additional injuries to the affected leg, such as injury to the popliteal artery (23%-32%) [6,26], compartment syndrome, injury to the tibial nerve [13,25,30], and more often injury to the common peroneal nerve (14%-40%) [3,14,16,21,28].…”
Section: Introductionmentioning
confidence: 99%